HVDC transmission across the Icelandic highlands - Einar Falur Zoega Sigurðsson 1987- (1987)
A technical feasibility study on an HVDC link connection between the North and the South coast of Iceland across the highlands. A study done with respect to improved stability of the Icelandic transmission system and increased opportunities in load control. Simulations and analysis are carried out in the PSS/E software on a complete model of the Icelandic transmission system, as well a system validation to a real event. Dynamic analysis on the system led to the conclusion that the Icelandic transmission system is in need of an upgrade, especially because of near future energy development, as well as with respect to the fact that the system has been few sizes to small for the last years. The results show that the interconnection between North and South Iceland is very important to the system for damping power oscillations in the ring connection as well as making the northern part of the system stronger. However, from economical and reliability point of view the AC highland option would be recommended, where the DC option has lower reliability, is very expensive and increases operation risks. However if the pricing of the system is ignored and Landsnet has to meet the demands of a longer cable connection over the highland to minimize the visual effects the HVDC link would be a good option especially with it’s power control capabilities. The results show that the HVDC link could solve all events generated with good results, considering that the system was made to monitor the right branch and given enough space to operate. Future recommendations are to develop a smart grid solution for the HVDC controller and to analyse, adjust geothermal generator response of the modelled Icelandic system. Tæknilegt hagkvæmnimat á HVDC hlekk milli norður og suður Íslands yﬁr miðhálendið. Rannsókn gerð með tilliti til bætts stöðugleika íslenska raforkukerﬁsins og aukinna möguleika á aﬂstjórnun. Hermanir og greiningar eru gerðar í PSS/E hugbúnaðinum á líkani af íslenska raforkukerfinu, ásamt fullgildingu módelsins. Greining á ...